Analysis of web worm attack on web application - Mohd. Ghazzali, Amalina (2008)
This study of web worms attack on web application can be implemented to enhance the security of current web application. Nowadays, attack from worms and viruses on web application come with several motives, whether to gain administrative access or even for stealing. This can be happening from a simple attack which will lead to a devastating effect to the organization. This analysis consists of several steps from analyzing worms attack to producing a guideline for secure web application development. The worms attack is based on a web application model developed using PHP as programming language and using MySQL database. In this case, the vulnerabilities found on the web application will be match to the method of attack from worms, and finally come out with a guideline to prevent such attacks. Even this guideline will not hundred percent prevent the attack, hopefully for anyone who follow this guideline will be on the safer side and at least minimized the possibility of attack to happen on their web application. Finally, the guideline produce from this analysis can be use for developing a secure web application. This guideline will be a framework for those who are new in this field to prevent themselves from being a targeted attack from this internet attacks.